STUDY OF A PROTOCOL FOR DETERMINING AUTOXIDATION IN LIPIDS OF FRESHWATER FISH PRODUCTS - Medina, J.R.; Melica, A.; Lorenzati, J.; Pérez, G.A. (Nexo Revista Científica, 2017)
In Argentina, the species of freshwater river more abundant but without commercial value is the sábalo (Prochilodus platensis), for that reason have been developed technologies of use of this species. However, its higher lipid value compared to sea fish accelerates the oxidation process, affecting its properties and sensory quality. Here, a suitable methodological scheme will be implemented to evaluate the autoxidation in the fresh muscle of unprocessed sardine and its protein concentrate, both conserved at -20ºC, following the deterioration according to the peroxide index, compounds reactive to thiobarbituric acid and heminic iron. It was found that the determination of TBARS is more efficient the color development at boiling temperatures, and an increase in the concentration of the TBA reagent does not significantly improve the absorbance signal. The presence of cryoprotectants is a limitation to the TBARS technique, which causes significant interference. The heminic iron level presents a proportional decrease according to the incubation time and the cooking of the samples. The levels of peroxides in samples of fresh muscle and surimi are very low, implying that if conservation is controlled this deterioration is avoided